Epstein-Barr Virus-negative Marginal Zone Lymphoma as an Uncommon Form of Monomorphic Posttransplant Lymphoproliferative Disorder. (October 2020) - Galera, Pallavi; Flavin, Richard; Savage, Natasha M.; Saksena, Annapurna; Gong, Shunyou; Wang, Huan-You; Swan, Niall; Xi, Liqiang; Raffeld, Mark; Pittaluga, Stefania; Jaffe, Elaine S.
Abstract : Monomorphic posttransplant lymphoproliferative disorders have been defined as lymphoid or plasmacytic proliferations that fulfill criteria for one of the B-cell or T/NK-cell neoplasms recognized in immunocompetent hosts in the current WHO Classification. Low-grade B-cell neoplasms have historically been excluded from this category, although rare reports of marginal zone lymphoma (MZL) have been described. We report 9 cases of posttransplant Epstein-Barr virus-negative MZL, all arising in solid organ transplant recipients (4 renal, 3 liver, 1 cardiac, and 1 liver, pancreas, and small bowel). Seven were extranodal MZL of mucosa-associated lymphoid tissue type, all of which had gastrointestinal involvement (4 colon, 1 duodenum, 1 stomach, and 1 oropharynx/base of tongue). Notably, the preferential involvement of intestine distinguishes posttransplant extranodal MZL from sporadic cases. Immunoglobulin light-chain restriction was seen in all cases, with polymerase chain reaction showing a monoclonal pattern in 7 of 8 cases with successful amplification of polymerase chain reaction products. A clonally unrelated recurrence was seen in one case. Next-generation sequencing identified recurrent mutations previously reported in MZL in 3/5 cases. MZL was diagnosed at least 1 year after solid organ transplant (median time to presentation, 84 mo; range, 13 to 108 mo). The median age was 44 (range, 9 to 73 y); the male: female ratio was 5:4. The mean follow-up was 33.4 months, with an indolent clinical course observed. A subset responded to reduction in immunosuppression and anti-CD20 therapy alone. These data support the designation of Epstein-Barr virus-negative MZL as an uncommon form of monomorphic posttransplant lymphoproliferative disorders.